2019
DOI: 10.1007/s10530-019-02041-6
|View full text |Cite
|
Sign up to set email alerts
|

The invasive red swamp crayfish (Procambarus clarkii) increases infection of the amphibian chytrid fungus (Batrachochytrium dendrobatidis)

Abstract: Emerging infectious diseases are increasingly recognized as a severe threat to wildlife. Chytridiomycosis, caused by Batrachochytrium dendrobatidis (Bd), is considered one of the most important causes for the decline of amphibian populations worldwide. Identifying potential biological reservoirs and characterizing the role they can play in pathogen maintenance is not only important from a scientific point of view, but also relevant from an applied perspective (e.g. disease control strategies), especially when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 43 publications
0
11
0
2
Order By: Relevance
“…Crustaceans have been proposed as alternative B. dendrobatidis hosts, having demonstrated their capacity to infect tadpoles (79). In Spain, the occurrence of B. dendrobatidis DNA in crayfish guts is related to the presence of B. dendrobatidis in amphibians (89). However, Betancourt-Roman et al (10) could not reproduce B. dendrobatidis persistence in crayfish, bringing into question the role of invertebrates as alternative hosts.…”
Section: Environment and Batrachochytrium Virulencementioning
confidence: 99%
“…Crustaceans have been proposed as alternative B. dendrobatidis hosts, having demonstrated their capacity to infect tadpoles (79). In Spain, the occurrence of B. dendrobatidis DNA in crayfish guts is related to the presence of B. dendrobatidis in amphibians (89). However, Betancourt-Roman et al (10) could not reproduce B. dendrobatidis persistence in crayfish, bringing into question the role of invertebrates as alternative hosts.…”
Section: Environment and Batrachochytrium Virulencementioning
confidence: 99%
“…Nonetheless, there are endemic species of amphibians that may suffer due to the presence of this new invasive alien species in their fresh waters. For instance, Souty-Grosset et al [ 68 ] and Oficialdegui et al [ 69 ] showed that crayfish eat amphibian eggs and tadpoles. Additionally, competition for food could also indirectly reduce amphibian populations, as the grazing activity that crayfish exert on periphyton may lead periphyton-associated invertebrates to disappear [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…If the lack of other urodele species and the scarcity of anuran hosts in the Lyciasalamandra range would imply absence of suitable pathogen reservoirs, infection and disease dynamics can be expected to be density dependent [ 26 , 29 ], rendering population extirpation less likely. However, current knowledge does not allow the exclusion of the presence of non-amphibian pathogen reservoirs, which may be biotic (for example invertebrate pathogen reservoirs as proposed for B. dendrobatidis [ 30 , 31 ] or abiotic (long term survival of resistant fungal spores). Abiotic reservoirs should maintain sufficient humidity levels and suitable temperatures for B. salamandrivorans to survive.…”
Section: Discussionmentioning
confidence: 99%